2009
DOI: 10.1088/0029-5515/49/9/095015
|View full text |Cite
|
Sign up to set email alerts
|

Integrated simulation of ELM energy loss and cycle in improved H-mode plasmas

Abstract: The energy loss due to an edge localized mode (ELM) crash and its cycle have been studied by using an integrated core transport code with a stability code for peeling–ballooning modes and a transport model of scrape-off-layer (SOL) and divertor plasmas. The integrated code reproduces a series of ELMs with the following characteristics. The ELM energy loss increases with decreasing collisionality and the ELM frequency increases linearly with the input power, as seen in experiments of type-I ELMs. A transport mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…This integrated code reproduced the experimentally observed collisionality dependence of ELM energy loss and showed that the collisionality dependence is caused by the bootstrap current, the SOL parallel conductive transport and the equipartition effect [28]. The integrtated code also clarified that the steep pressure gradient inside the top of pedestal enhances the ELM energy loss [31], which is validated by the experimental data in JT-60U [32].…”
Section: Integrated Edge/pedestal Model For Study Of Pellet Triggeredsupporting
confidence: 72%
“…This integrated code reproduced the experimentally observed collisionality dependence of ELM energy loss and showed that the collisionality dependence is caused by the bootstrap current, the SOL parallel conductive transport and the equipartition effect [28]. The integrtated code also clarified that the steep pressure gradient inside the top of pedestal enhances the ELM energy loss [31], which is validated by the experimental data in JT-60U [32].…”
Section: Integrated Edge/pedestal Model For Study Of Pellet Triggeredsupporting
confidence: 72%
“…The increase of the surface current (i.e. edge bootstrap current) destabilize lower n (toroidal mode number) peeling eigenmode, which has larger radial extent [22]. Mitigation of ELM strength becomes essential for ITER and especially for future DEMO reactor, which necessarily operates high duty factor to effectively breed tritium.…”
Section: Elm Heat Load By High Edge Pedestalmentioning
confidence: 99%
“…Independence of each module is almost kept and therefore model improvement or implementation of new model become possible with small effort. The MPMD system has been already introduced to the integration of the SONIC suite and the 1.5 D core transport code TOPICS [18][19][20] and the time evolution of the L-H transition has been successfully simulated selfconsistently [21,22]. Recently, the MPMD system has been improved mainly in the viewpoint of the data exchange method and restructuring of the SONIC suite, i.e., SOL-DOR/NEUT2D/IMPMC, on the new MPMD system is ongoing.…”
Section: (Iii) Development Of Mpmd Parallel Computing Systemmentioning
confidence: 99%